2009
DOI: 10.1016/j.ijgo.2009.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Obstetricians' opinions and attitudes toward maternal refusal of recommended cesarean delivery in Nigeria

Abstract: The possibility of providing emergency obstetric care would remove many indications for cesarean delivery from the list of absolute indications in Nigeria; and management guidelines would protect obstetricians in the event of litigation, and improve their acceptance and respect of maternal choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…However, in some countries, including Nigeria, due to economic problems, one fourth of women do not accept performing CS even in emergency situations (23). A study showed that only 2.5% of deliveries in the USA in 2003 were performed using CS based on women's request (24).…”
Section: Introductionmentioning
confidence: 99%
“…However, in some countries, including Nigeria, due to economic problems, one fourth of women do not accept performing CS even in emergency situations (23). A study showed that only 2.5% of deliveries in the USA in 2003 were performed using CS based on women's request (24).…”
Section: Introductionmentioning
confidence: 99%
“…These debates about the status of the fetus are relevant here insofar as they reflect how clinicians' views on the fetus may influence women's care. Most empirical research about pregnant women who decline recommended care has been devoted to refusal of caesarean section (CS; see Adams et al, 2003;Chigbu et al, 2009;Chigbu & Iloabachie, 2007;Cuttini et al, 2006;Danerek et al, 2011;Samuels et al, 2007) and, to a lesser extent, blood products (see Iris et al, 2009;van Wolfswinkel et al, 2009). Studies examining other maternal refusals are rare.…”
Section: Delimiting the Scopementioning
confidence: 99%
“…A similar study (Chigbu et al, 2009) explored the attitudes of obstetricians in Nigeria to several hypothetical scenarios, all involving maternal refusal of recommended CS. Obstetricians expressed the opinion that ongoing counselling was their preferred way of "managing" maternal refusals, but resource constraints were likely to lead them to "insist on planned caesarean delivery" (Chigbu et al, 2009, p250).…”
Section: Obstetricians' Attitudesmentioning
confidence: 99%
See 2 more Smart Citations